PALEOGENE PALEOCLIMATE RECONSTRUCTION USING OXYGEN ISOTOPES FROM LAND AND FRESHWATER ORGANISMS: THE USE OF MULTIPLE PALEOPROXIES - Grimes S.T.; Mattey D.P.; Hooker J.J.; Collinson M.E. (My University, 2003)
Understanding past climate change is critical to the interpretation of earth history. Even though relative temperature change has been readily assessed in the marine record, it has been more difficult in the terrestrial record due to restricted taxonomic distribution and isotopic fractionation. This problem could be overcome by the use of multiple paleoproxies. Therefore, the δ18O isotopic composition of five paleoproxies (rodent tooth enamel, δ18OPhosphate = +17.7 +/- 2.0%% n = 74 (VSMOW); fish scale ganoine δ18OPhosphate = +19.7 +/- 0.7%% n = 20 (VSMOW); gastropod shell δ18OCalcite = -1.7 +/- 1.3%% n = 50 (VPDB); charophyte gyrogonite δ18OCalcite = -2.4 +/- 0.5%% n = 20 (VPDB); fish otolith δ18OAragonite = δ18O = -3.6 +/- 0.6%% n = 20 (VPDB)) from the Late Eocene (Priabonian) Osborne Member (Headon Hill Formation, Solent Group, Hampshire Basin, UK) were determined. Because diagenetic alteration was shown to be minimal the phosphate oxygen component of rodent tooth enamel (as opposed to enamel carbonate oxygen) was used to calculate an initial δ18OLocal water value of 0.0 +/- 3.4%%. However, a skewed distribution, most likely as a result of the ingestion of evaporating water, necessitated the calculation of a corrected δ18OLocal water value of -1.3 +/- 1.7%% (n = 62). This δ18OLocal water value corresponds to an approximate mean annual temperature of 18 +/- 1°C. Four other mean paleotemperatures can also be calculated by combining the δ18OLocal water value with four independent freshwater paleoproxies. The calculated paleotemperature using the fish scale thermometry equations most likely represents the mean temperature (21 +/- 2°C) of the entire length of the growing season. This should be concordant with the paleotemperature calculated using the Lymnaea shell thermometry equation (23 +/- 2°C). The lack of concordance is interpreted to be the result of diagenetic alteration of the originally aragonitic Lymnaea shell to calcite. The mean paleotemperature calculated using the charophyte gyrogonite thermometry equation (21 +/- 2°C), on the other hand, most likely represents the mean temperature of a single month toward the end of the growing season. The fish otolith mean paleotemperature (28 +/- 2°C) most likely represents the mean temperature of the warmest months of the growing season. An approximate mean annual temperature of 18 +/- 1°C, in addition to a mean growing season paleotemperature of 21 +/- 2°C (using fish scale only) with a warmest month temperature of 28 +/- 2°C, and high associated standard deviations suggest that a subtropical to warm temperate seasonal climate existed during the deposition of the Late Eocene Osborne Member.
Keywords: Priabonian; Cenozoic::Paleogene::Eocene::Priabonian; Кайнозой::Палеоген::Эоцен::Приабонский